Inpatient cognitive behaviour therapy for anorexia nervosa: a randomized controlled trial. - Dalle Grave, R; Calugi, S; Conti, M; Doll, H; Fairburn, C (2013)
BACKGROUND: The aim of this study was to compare the immediate and longer-term effects of two cognitive behaviour therapy programmes for hospitalized patients with anorexia nervosa, one focused exclusively on the patients' eating disorder features and the other focused also on mood intolerance, clinical perfectionism, core low self-esteem or interpersonal difficulties. Both programmes were derived from enhanced cognitive behaviour therapy (CBT-E) for eating disorders. METHODS: Eighty consecutive patients with severe anorexia nervosa were randomized to the two inpatient CBT-E programmes, both of which involved 20 weeks of treatment (13 weeks as an inpatient and 7 as a day patient). The patients were then followed up over 12 months. The assessments were made blind to treatment condition. RESULTS: Eighty-one percent of the eligible patients accepted inpatient CBT-E, of whom 90% completed the 20 weeks of treatment. The patients in both programmes showed significant improvements in weight, eating disorder and general psychopathology. Deterioration after discharge did occur but it was not marked and it was restricted to the first 6 months. There were no statistically significant differences between the effects of the two programmes. CONCLUSIONS: These findings suggest that both versions of inpatient CBT-E are well accepted by these severely ill patients and might be a viable and promising treatment for severe anorexia nervosa. There appears to be no benefit from using the more complex form of the treatment.